Results from a large multinational clinical trial (guardian™3) using prophylactic treatment with turoctocog alfa in paediatric patients with severe haemophilia A: safety, efficacy and pharmacokinetics. (8th May 2013) - Kulkarni, R.; Karim, F. A.; Glamocanin, S.; Janic, D.; Vdovin, V.; Ozelo, M.; Rageliene, L.; Carboni, E.; Laguna, P.; Dobaczewski, G.; Seremetis, S.; Lindblom, A.; et al.
Summary: Recombinant factor VIII (rFVIII) products provide a safe and efficacious replacement therapy for prophylaxis and treatment of bleeding episodes in patients with severe haemophilia A. This multinational, open‐label, non‐controlled trial investigated the safety, efficacy and pharmacokinetics (PK) of turoctocog alfa, a new rFVIII product, in a paediatric population. The primary objective was to evaluate safety. A total of 31 younger children (0–5 years) and 32 older children (6–11 years), with ≥50 exposure days to any factor VIII (FVIII) product and no history of inhibitors, received prophylaxis with turoctocog alfa (25–50 IU kg −1 every second day or 25–60 IU kg −1 three times weekly). PK assessments of turoctocog alfa and the patients' previous FVIII product were performed in 28 patients. Mean exposure to turoctocog alfa was 60 exposure days per patient. This corresponds to approximately 4.5 months in the trial. None of the patients developed inhibitors (≥0.6 BU) and no safety concerns were raised. A total of 120 bleeding episodes (95%) were controlled with 1–2 infusions of turoctocog alfa. Based on patient reports, the success rate (defined as 'excellent' or 'good' haemostatic response) for treatment of bleeding episodes was 92%. Overall, the median annualized bleeding rate was 3.0 (interquartile range: 8.5) bleeds patient −1 year −1 . PK parameters were comparable between the two age groups. In conclusion, the present large global clinical trial showed that turoctocog alfa was safe, effective in treatment of bleeding episodes and had a prophylactic effect in paediatric patients.